UPAYA MENINGKATKAN HASIL BELAJAR SAINS DENGAN METODE DISKUSI PADA SISWA KELAS V SD NEGERI 011 BUKIT KAPUR - Zambri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low science learning outcomes of fifth-grade students at SD Negeri 011 Bukit Kapur. The study aims to improve the science learning outcomes of these students by using the discussion method. The subjects of this study were 35 fifth-grade students of SD Negeri 011 Bukit Kapur. This research is a classroom action research conducted in two cycles. The research parameters include student learning outcomes consisting of absorption, mastery learning, student learning activities, and teacher teaching activities. The results showed that in the first cycle, the average daily test score was 69.71% (Fair), and in the second cycle, the average daily test score increased to 78% (Good). Mastery learning also improved, from 82.86% in the first cycle to 94.28% in the second cycle. Student activity in the learning process increased from 73.98% (Fair) in the first cycle to 73.09% (Fair) in the second cycle. Meanwhile, teacher activity in the learning process improved from 92.5% (Very Good) in the first cycle to 96% (Very Good) in the second cycle. Based on these results, it can be concluded that the discussion method can improve the science learning outcomes of fifth-grade students at SD Negeri 011 Bukit Kapur.